A quantitative assessment and process analysis of the contribution from meteorological conditions in an O3 pollution episode in Guangzhou, China. (15th June 2023) - Xu, Yifei; Shen, Ao; Jin, Yinbao; Liu, Yiming; Lu, Xiao; Fan, Shaojia; Hong, Yingying; Fan, Qi
Abstract: Ozone plays a significant role in the troposphere due to its influence on human health, air pollution, and global warming. Despite the decline of NOx and VOCs in China in recent years, obvious increases in O3 concentration took place, while the attributions to it remained unclear. Previous studies have revealed that the contribution of meteorological conditions is getting increasingly significant to O3 concentration. Given that O3 concentration continued to climb in China, the influence of meteorology on O3 concentration should not be neglected. In this study, the WRF-CMAQ model was utilized to study an O3 episode in the Pearl River Delta (PRD) region, China. In this short-term simulation, anthropogenic emissions remained unchanged during the Polluted Week (PW) compared with the Clean Week (CW), which allowed us to investigate the effects of changes in meteorological conditions (ΔMET) on O3 variations via an efficient method of sensitivity experiment. And the contribution of changes in anthropogenic emissions (ΔEMIS) was evaluated similarly. It turns out that ΔMET explained 85.8% of the elevated O3 concentration in urban Guangzhou (GZ), which resulted from an increase in temperature and solar radiation, and a decrease in wind speed and humidity, while ΔEMIS explained 13.3%. We also analyzed the 3-dimensional development process of the O3 pollution and quantitatively assessed it by process analysis in the CMAQ model. Meteorology affected O3 concentration through both chemical reactions and physical processes, with the former contributing 36.9% and the latter 63.1%. Most of the elevated O3 was found near the surface at a height less than 50 m above the ground, which accounted for 56.8%. This study emphasized the contribution of meteorological conditions to O3 concentration and demonstrated a streamlined method of sensitivity experiment to quantitatively identify the impact of meteorology, which could be useful for O3 prevention and emissions reduction strategies. Graphical abstract: Image 1 Highlights: Meteorologically- and Anthropogenically-driven O3 variations in Guangzhou were investigated. The method is applicable for assessing contribution from meteorology on a short-time scale. Contributions of physical and chemical processes, and of different heights to O3 were estimated.